METODE SQ3R SEBAGAI UPAYA MENINGKATKANKEMAMPUAN MEMBACA PEMAHAMAN BAHASA INGGRISSISWA KELAS XI IPA SMA ISLAM 3 SLEMAN - Annisa Nurul Ilmi, Annida Nurul F. A., dan Fauzan Ibram M. (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
The research is aimed to improve the students’ English reading comprehensionskills of Grade XI IPA at SMA Islam 3 Sleman Yogyakarta.The subjects of the research were 17 students. This research focused on theimplementation of SQ3R method to improve the students’ reading comprehension skills.The research was done in two cycles. Each cycle was divided into four steps, i.e planning,acting, reflecting, and evaluating. The data were collected by observations, field notes,interviews, questionnaires, and documentations. The data were analized usingquantitative and qualitative interpretations. The succeed of the research were achievedbased on some criteria related to the students’ or teacher’s improvement changes.The result of the research shows that the improvement happened on six aspectsthat become reading comprehension criteria, i.e determining main ideas or topic sentence,recognizing detail information, mastering vocabularies and grammar, searching implicitand explicit information in texts. The improvements can be seen through the averagescores in each criterion. The average score in English reading comprehension skillsbefore the action was 27.64. The score in the first action was 33.52 and that in thesecond cycle was 40. It can be concluded that the improvement was 21.27% from pretestto the first cycle, 19.33% from the first cycle to the second cycle and 44.71% frompre-test until the last cycle. The improvement in each criterion was determining mainidea or topic (33.96%), recognizing detail information (68.57%), mastering vocabulary(85.71%), mastering grammar (28.81%), searching implicit information in a text (51.06%),and explicit information (25.53%).Keywords: English Reading Comprehension Skills, Grade XI IPA at SMA Islam 3 SlemanYogyakarta, SQ3R.